A new species of ldiocelyphus Malloch (Diptera, Celyphidae) from the Philippine Islands - Nartshuk, Emilia (Entomologica Fennica, 1996)
A new species Idiocelyphus freyi is described from Mindanao, the Philippine Islands. Male genitalia are illustrated. The new species is included in the key of the species of Idiocelypus.